2017
DOI: 10.1038/s41598-017-05767-2
|View full text |Cite
|
Sign up to set email alerts
|

Safe Brain Tumor Resection Does not Depend on Surgery Alone - Role of Hemodynamics

Abstract: Aim of this study was to determine if perioperative hemodynamics have an impact on perioperative infarct volume and patients’ prognosis. 201 cases with surgery for a newly diagnosed or recurrent glioblastoma were retrospectively analyzed. Clinical data and perioperative hemodynamic parameters, blood tests and time of surgery were recorded. Postoperative infarct volume was quantitatively assessed by semiautomatic segmentation. Mean diastolic blood pressure (dBP) during surgery (rho −0.239, 95% CI −0.11 – −0.367… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 27 publications
0
10
2
Order By: Relevance
“…We did not detect any additional peri-operative parameters to be associated with the occurrence of rim restriction, including previously reported ones, such as recurrent operations and decreased MAP or IOM abnormalities (Tables 1 and 2 ). 15 , 25 , 26 , 29 Findings of rim restriction have been associated with evidence of remnant blood products in the surgical cavity on postoperative imaging, yet no significant association were seen in our study 9 , 30 .…”
Section: Discussioncontrasting
confidence: 52%
“…We did not detect any additional peri-operative parameters to be associated with the occurrence of rim restriction, including previously reported ones, such as recurrent operations and decreased MAP or IOM abnormalities (Tables 1 and 2 ). 15 , 25 , 26 , 29 Findings of rim restriction have been associated with evidence of remnant blood products in the surgical cavity on postoperative imaging, yet no significant association were seen in our study 9 , 30 .…”
Section: Discussioncontrasting
confidence: 52%
“…It is still not clear what measures can be taken to minimize the risk of infarctions in relation to tumor surgery. In a study exploring the relationship between perioperative hemodynamics, postoperative infarctions, and overall survival, diastolic blood pressure, a positive liquid balance, and duration of surgery were associated with postoperative infarction volumes [3]. Our data suggest a correlation between perioperative bleeding and infarction volume.…”
Section: Discussionmentioning
confidence: 52%
“…However, the relative importance of these factors is unknown. Several studies emphasize the importance of infarction volume [2][3][4], but even small ischemic lesions in eloquent locations may result in severe neurological sequelae [18]. Further, little is known about the risk of ischemic lesions in relation to surgical technique, e.g., use of suction vs. ultrasonic aspirator, subpial dissection vs. transsulcal approaches, outsidein vs. in-side-out resections, and more.…”
Section: Discussionmentioning
confidence: 99%
“…21,38 It was suggested that strict control of blood pressure and fluid balance by the anesthesiologist may assist in decreasing the risk for stroke during surgery. 5 We found that low MAP at the beginning of surgery correlates with a higher rate of intraoperative strokes. Whether raising MAP by preoperative hydration can decrease the rate of stroke should be further studied.…”
Section: Intraoperative Indicators Of Strokementioning
confidence: 61%